Computed tomography of bowel obstruction: tricks of the trade. (December 2015) - Galia, Massimo; Agnello, Francesco; La Grutta, Ludovico; Lo Re, Giuseppe; Cabibbo, Giuseppe; Grassedonio, Emanuele; Gioia, Bruno Giuseppe; Sparacia, Gianvincenzo; Lo Casto, Antonio; Lagalla, Roberto; Midiri, Massimo
Abstract : Bowel obstruction (BO) is a frequent cause of hospitalization and surgical consultation for acute abdominal pain. It is usually suspected at physical examination, but clinical and laboratory data are often nonspecific. Thus, computed tomography plays a crucial role in a correct diagnosis of BO. Indeed, computed tomography can confirm a diagnosis of BO, and identify the location and cause of the obstruction. In this review, the computed tomography appearances of common and uncommon causes of BO and pseudo-obstruction are reviewed.